are you asking for the derivative of dy squared with respect to x squared when x squared times y squared equals 9?
Because your notation is confusing
2006-10-23 03:51:53
·
answer #1
·
answered by shinobisoulxxx 2
·
0⤊
0⤋
(x^2)(y^2)=9
the first deriv is
2x y^2 +x^2 2y dy/dx=0
arrange it dy/dx =-2yxy^2/(2yx^2) cancle out
u get dy/dx = -y/x
now u need the secod deriv
d^2y/dx^2 = ((-dy/dx x ) - (-y))/x^2
as we know the value of dy/dx =-y/x so subtitute in the second deriva
u get
d^2y/dx^2 = ((y/x)x+ y)/x^2 ==>
=> d^2y/dx^2 =2y/x^2
2006-10-23 06:11:06
·
answer #2
·
answered by Khalidxp 3
·
0⤊
0⤋
y^2=9/x^2
on differentiating with respect to x
2y(dy/dx)=9*(-2)(1/x^3)=-18/x^3
dy/dx=18/(2x^3y)=9/(x^3 y)
d^2y/dx^2=(3x^2+x^3 dy/dx) / (x^6 y^2)........2
substituting dy/dx in 2
d^2y/dx^2=(3x^2 y+9) / (x^6 y ^2)
tats it !!!!!!!!!!!
2006-10-23 04:21:57
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
i think your notation is fine. easiest to do it this way:
rewrite as:
y^2=9x^(-2)
2y*dy/dx=-18x^(-3) - differentiating once
2y*(d^2y/dx^2)+ 2(dy/dx) * (dy/dx) = 54x^(-4)
so, grouping terms,
2y(d^2y/dx^2) + 2[dy/dx]^2 - 54x^(-4) = 0
i.e. (d^2y/dx^2) + [dy/dx]^2 - 27x^(-4) = 0
you can rearrange to put d^2y/dx^2 = something if u like
2006-10-23 04:09:28
·
answer #4
·
answered by tsunamijon 4
·
0⤊
0⤋
y^2=9x^-2
so y= 3x^-1
differentiating
dy/dx = -3x^-2
once more differntiating
d^2y/dx^2 = 6x^-3
2006-10-23 05:36:20
·
answer #5
·
answered by grandpa 4
·
0⤊
0⤋
(2*y^2) + (2*x^2) + 8*x*y
2006-10-23 03:51:19
·
answer #6
·
answered by karandeep singh d 1
·
0⤊
0⤋
characters in a cloud for swearing, in a comic strip.
2006-10-23 03:52:48
·
answer #7
·
answered by COSMO 4
·
0⤊
0⤋
its bollocks
2006-10-23 03:46:16
·
answer #8
·
answered by musicman 3
·
0⤊
2⤋